2019
DOI: 10.1002/uog.20211
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive perinatal and pediatric autopsy with laparoscopically assisted tissue sampling: feasibility and experience of the MinImAL procedure

Abstract: Objective Less invasive autopsy techniques in cases of fetal or infant death have good acceptability among parents, but the published sampling adequacy in needle biopsy studies is generally poor. Minimally Invasive Autopsy with Laparoscopically assisted sampling (MinImAL) has the potential to increase the diagnostic yield of less invasive autopsy by improving the quality and quantity of tissue samples obtained, whilst permitting visualization, extraction and examination of internal organs through a small incis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(49 reference statements)
0
24
0
1
Order By: Relevance
“…Determination of causes remains challenging due to the pathophysiological interaction between mother, foetus and placenta and multiple co-existing conditions that can contribute [31,32]. Previous studies have shown that diagnostic assessments, such as post-mortem autopsy or minimal invasive perinatal autopsy, reduced the percentage of unexplained deaths [32][33][34][35]. Global consensus on standardisation of necessary diagnostic assessments in stillbirths would not only improve classifications globally but also motivate healthcare providers, researchers and policymakers to reduce preventable stillbirths.…”
Section: Discussionmentioning
confidence: 99%
“…Determination of causes remains challenging due to the pathophysiological interaction between mother, foetus and placenta and multiple co-existing conditions that can contribute [31,32]. Previous studies have shown that diagnostic assessments, such as post-mortem autopsy or minimal invasive perinatal autopsy, reduced the percentage of unexplained deaths [32][33][34][35]. Global consensus on standardisation of necessary diagnostic assessments in stillbirths would not only improve classifications globally but also motivate healthcare providers, researchers and policymakers to reduce preventable stillbirths.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive examinations were performed in 29 of 236 fetuses (12.3%), which included a full conventional autopsy in 17 fetuses (58.6%), an MIA in 7 (24.1%) (this subset has also been reported in previous publications 20,21 ), and a limited autopsy in 5 (17.2%).…”
Section: Diagnostic Accuracymentioning
confidence: 88%
“…Original Research OBSTETRICS ajog.org were conducted through either ultrasound-guided 20 or laparoscopic-guided biopsy techniques. 21 In our department, a death classification system is not used routinely, although a narrative exploration of findings linked to clinical history is provided in the final autopsy report.…”
Section: What Does This Add To What Is Known?mentioning
confidence: 99%
“…Ultrasound-guided biopsies are more successful (76.1%) and can be performed via the umbilical vein mitigating incisions to the body [ 36 ]. Laparoscopically guided tissue sampling yields the highest success rates (> 80%) [ 37 ] but can be difficult to perform in small foetuses, and necessitates small incisions and more expensive equipment not commonly found in many mortuaries. It is important prior to conducting any tissue sampling that parental consent has been provided for this.…”
Section: When Would Additional Tissue Sampling Be Beneficial Over Imaging Alone?mentioning
confidence: 99%